PELAKSANAAN PRINSIP KEHATI-HATIAN DALAM PERJANJIAN PEMBIAYAAN KONSUMEN OLEH PT. CENTERAL SANTOSA FINANCE PEKANBARU - ANDRI KURNIAWAN; Firdaus '; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
In the practice of daily life financial institutions that are not known by the public is a foreign bank. In order to channel the funding requirements needed society, it appears that an alternative financing institutions raised funds more flexible and moderate than banks in certain cases even higher level of risk. Financial institutions that offer models of new formulations in terms of channeling funds to those who need it as consumer financing, arranged by Presidential Decree No. 9 of 2009 on Financing Agency, PT. Centeral Santosa Finance Pekanbaru as a financial institution that has a product to accommodate the consumer in helping to vehicle financing.In this case relates to the implementation of the Precautionary Principle in consumer financing agreement by PT. Centeral Santosa Finance Pekanbaru. The purpose of this thesis, namely: First, This type of research can be classified into types soiologis juridical research, because this research author directly conduct research on location or a place to study provide complete and clear picture of the issues examined. This research was conducted at PT. Centeral Santosa Finance Pekanbaru, while the sample population is a whole party with regard to the problems examined, the data source used, primary data, secondary data, data collection techniques in this study with questionnaires, interviews and review of the literature.From the research problem there are two main things that can be inferred. First, the implementation of the Precautionary Principle by PT. Centeral Santosa Finance Pekanbaru in consumer financing agreement has not been run in accordance with applicable regulations. So the PT. Centeral Santosa Finance Pekanbaru do not pay attention to the precautionary principle as a risk management in credit financing. Due to the implementation of the precautionary principle as a formality without regard to legal aspects. Suggestions Writer, first, to the government, the government should make the legislation more specific. In terms of the application of the precautionary principle in consumer financing agreement, PT. Centeral Santosa Finance Pekanbaru branch does not run properly, it should in completing the requirements of consumer financing agreement, PT. Centeral Santosa Finance Pekanbaru branch reinforce any prospective customers to complete the requirements in accordance with the procedure.Keywords: Consumer Finance, Principles Of Prudence